Vitamin D and Age-Related Macular Degeneration - Layana, Alfredo Garcia (2017)
In recent years, the relationship between vitamin D and health has received growing attention from the scientific and medical communities. Vitamin D deficiencies have been repeatedly associated with various acute and chronic diseases, including age-related macular degeneration (AMD). Its active metabolite, 1α,25-dihydoxy vitamin D, acts as a modulator of cell proliferation, differentiation and apoptosis, and cumulative data from experimental and observational studies suggest that relatively a lower vitamin D status could be a potential risk factor for the development of early and/or late AMD. Herein, we made a narrative review of the mechanisms linking a potential role of vitamin D with the current concepts of AMD pathophysiology.